2010
DOI: 10.5713/ajas.2010.90446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multi-microbial Probiotics Produced by Submerged Liquid and Solid Substrate Fermentation Methods in Broilers

Abstract: Two experiments were conducted to evaluate multi-microbe submerged liquid (SLF) and solid substrate (SSF) fermented probiotic products in broilers. The SLF and SSF probiotics were comprised of Lactobacillus acidophilus (1.1×10 9 and 4×10 8 cfu/g), Bacillus subtilis (1.1×10 9 and 4.8×10 9 cfu/g), Saccharomyces cerevisiae (1.5×10 7 and 1.0×10 4 cfu/g) and Aspergillus oryzae (2.6×10 7 and 4.3×10 7 cfu/g), respectively. In Exp. 1, 640 day-old Ross chicks were allotted to 4 treatments, each comprising 4 replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 35 publications
11
65
1
Order By: Relevance
“…Probiotics beneficially affect the host animal by improving intestinal balance (Chen et al 2013), creating gut micro-ecological conditions that suppress harmful microorganisms like Clostridium and Coliforms (Shim et al 2010;Sinol et al 2012) and by favouring beneficial microorganisms like Lactobacillus and Bifidobacterium. In our study, the dietary supplementation of Bacillus subtilis DSM 17299, Clostridium butyricum and Lactobacillus acidophilus endospores increased gut Lactobacillus and Bifidobacteria counts and decreased Escherichia coli and Clostridium perfringens counts compared with those of other treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics beneficially affect the host animal by improving intestinal balance (Chen et al 2013), creating gut micro-ecological conditions that suppress harmful microorganisms like Clostridium and Coliforms (Shim et al 2010;Sinol et al 2012) and by favouring beneficial microorganisms like Lactobacillus and Bifidobacterium. In our study, the dietary supplementation of Bacillus subtilis DSM 17299, Clostridium butyricum and Lactobacillus acidophilus endospores increased gut Lactobacillus and Bifidobacteria counts and decreased Escherichia coli and Clostridium perfringens counts compared with those of other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in growth performance and feed efficiency of broiler chickens supplemented with different strains of probiotics (Sinol et al 2012;Zhang and Kim 2014) are thought to be induced by the cumulative effect of probiotic action including the improvement of feed intake and digestion (Shim et al 2010), increased digestive enzyme activity and decreased NH 3 production (Chen et al 2013), maintenance of beneficial microbial populations (Chen et al 2013) and alteration of bacterial metabolism (Sinol et al 2012). In this study, DM and N digestibility were increased by dietary supplementation of TSP.…”
Section: Discussionmentioning
confidence: 99%
“…The chicks were randomly divided into two experimental groups of 12 chicks in each group -Group 1 as the Control group and Group 2 as the Test group. Both the groups were fed broiler starter from day 1to 21 and broiler finisher from day 22 to 42 (Shim et al, 2010). Group 1 (Control) were provided only water and group 2 (Test) with water with 4.1x10 8 cfu/ml of B.aerius spore powder formulation added as per standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Most research findings on probiotics have demonstrated the use of mono strain or multi strain probiotic microbes belonging to the same species or genus (Shim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[5] defines the SSF as the culture of microorganisms in a particular substrate, allowing its growth and metabolism at proper temperature and aeration; this permits the use of microbial production or single-cell protein. In this sense, [6] mentions that the SSF consists in the growth of microorganisms on solid substrates in absence of free water; this improves the chemical composition of some by-products and generates new alternatives for animal feeding. However, there is not enough information on the fermentation in solid state of paper sludge with the addition of probiotics and considering its potential use in ruminant feeding.…”
Section: Introductionmentioning
confidence: 99%